2005
DOI: 10.1021/bi050814y
|View full text |Cite
|
Sign up to set email alerts
|

Binding, Domain Orientation, and Dynamics of the Lck SH3−SH2 Domain Pair and Comparison with Other Src-Family Kinases

Abstract: The catalytic activity of Src-family kinases is regulated by association with its SH3 and SH2 domains. Activation requires displacement of intermolecular contacts by SH3/SH2 binding ligands resulting in dissociation of the SH3 and SH2 domains from the kinase domain. To understand the contribution of the SH3-SH2 domain pair to this regulatory process, the binding of peptides derived from physiologically relevant SH2 and SH3 interaction partners was studied for Lck and its relative Fyn by NMR spectroscopy. In co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…However, the Lck SH3 domain orientation significantly differs from Hck and is rotated away from the SH2 domain by 100°relative to the Hck SH3 domain. This comparison demonstrates inter-domain flexibility across SFKs even in the crystal state and is consistent with 15 N NMR relaxation data that showed differences in correlation times between the SH3-SH2 domains of Fyn, Lck, and c-Abl (27,34,35).…”
Section: Relationship Of Sh3 and Sh2 Domains Within The Hck32lsupporting
confidence: 86%
“…However, the Lck SH3 domain orientation significantly differs from Hck and is rotated away from the SH2 domain by 100°relative to the Hck SH3 domain. This comparison demonstrates inter-domain flexibility across SFKs even in the crystal state and is consistent with 15 N NMR relaxation data that showed differences in correlation times between the SH3-SH2 domains of Fyn, Lck, and c-Abl (27,34,35).…”
Section: Relationship Of Sh3 and Sh2 Domains Within The Hck32lsupporting
confidence: 86%
“…Interestingly, the relative orientations of the SH3 and SH2 domains in our new structure are unique compared with those observed in these earlier SH3-SH2 structures (37,46,47), highlighting the variability in interdomain positioning among the Src-family kinases. In addition, 15 N NMR relaxation data show differences in correlation times between the SH3 and SH2 domains of Fyn, Lck, and c-Abl when these domains are joined (46,(52)(53)(54). Finally, NMR studies of Nef interaction with a Hck SH3-SH2-linker protein demonstrated significant chemical shift perturbations not only for residues in the Hck SH3 domain but also in the connector and N-terminal region of the SH2 domain upon Nef binding (55).…”
Section: Resultsmentioning
confidence: 94%
“…In these experiments, chemical shift changes were monitored in the domain not involved in the direct binding of the peptide ligand. NMR studies of Fyn, c-Src, and Lck SH32 proteins revealed that peptide ligand binding to the SH2 domain resulted in either small (c-Src, Fyn) [75 -77] or undetectable (Lck) [78] chemical shift changes in the SH3 domain, again suggesting that SH2 ligation is not structurally communicated to the SH3 domain. Together, the HXMS and NMR results are consistent with the idea that SFK SH3 and SH2 domains have independent folding and binding activity which is not grossly influenced by being next to one another in sequence.…”
Section: Biophysical Studies Of Sfk Dynamicsmentioning
confidence: 99%